Bilateral Spontaneous Pneumothorax in Chronic Silicosis: A Case Report. (15th March 2014) - Mishra, Pritinanda; Jacob, Sajini Elizabeth; Basu, Debdatta; Panigrahi, Manoj Kumar; Govindaraj, Vishnukanth
Abstract : Silicosis is an occupational lung disease caused by inhalation of crystalline silica. People working in occupations like sandblasting, surface drilling, tunneling, silica flour milling, ceramic making, and so forth are predisposed to develop silicosis. Crystalline forms of silica are more fibrogenic than the amorphous forms, highlighting the importance of the physical form in pathogenesis. Lung biopsy is rarely performed for the diagnosis of silicosis as it can easily be detected by occupational history and radiological features. Patients with silicosis can develop complications like tuberculosis, lung cancer, progressive massive fibrosis, cor pulmonale, broncholithiasis, or tracheobronchial compression by lymph nodes. Pleural involvement in silicosis is rare. Spontaneous pneumothorax is a pleural complication that can develop in such patients. Usually in silicosis pneumothorax is unilateral. We hereby report the lung biopsy findings and discuss the mechanism of pneumothorax development in a case of chronic silicosis who, later on died during the course of the disease.